Processo de construção da ontologia de registros acadêmicos do modelo educacional brasileiro – ONTO-RA - OLIVEIRA, Márcio Melo de (2014)
The autonomy of federal educational institutions in Brazil hindered the creation of a centralized system that was responsible for the academic management of the administrative purview of the Ministry of Education institutions - MEC. This scenario provided that each institution should seek to develop their own solution of academic management system and that the MEC would use different data collection systems to obtain information about the actions of the institutions. All this occurred without there being any motion or recommendation for the definition of guidelines for the construction of these systems or something that generates semantic uniformity in the field of Brazilian academic records. This has created heterogeneous systems and unreliable statistics. Based on the layouts for systems migration data collection, the Law of Guidelines and Bases of Education - LDB and other artifacts such as the Statement of Goals and Commitments Agreement - TAMC is proposed in this dissertation ONTOLOGY OF ACADEMIC RECORDS BRAZILIAN MODEL EDCUAÇÃO - ONTOR-RA. This ontology used these artifacts, ranked in Engineering Ontology as a Resource Ontological not, in order to generate semantic uniformity required for systems of data collection and academic management can be adjusted and new systems to be built is based on this model. The construction of the ONTO-RA, had the definition of a method of evaluation of methodologies for building ontologies available, which resulted in the choice of methodology NEON. This methodology was applied with minor adjustments to the construction of the proposed ontology. This paper also presented an application of the ontology which aims to highlight its effectiveness as a basis for setting the systems from the semantic uniformity obtained. In this application, for each requirement of ONTO-RA was analyzed care of the same for the collection SISTEC, EDUCANCENSO data systems, and CENSUS OF HIGHER EDUCATION - CENSUP. The SICAD and SIGA systems, which are academic management systems currently in operation at the Federal Institute of Education Bahia - IFBA were also analyzed. This study revealed that several important academic indicators are being generated incorrectly due to the various inadequacies identified, since the percentage of requirements not met ranged between 2% and 37% in the analyzed systems.